Piloting a multidisciplinary approach to improve outcomes of fetal whole exome sequencing: An overview of workflow and case example. (19th February 2023) - Micke, Kestutis C.; Elfman, Hannah M.; Fantauzzo, Katherine A.; McGrath, Patrick S.; Clouthier, David E.; McCandless, Shawn E.; Larson, Austin; Putra, Manesha; Cuneo, Bettina F.; Reynolds, Regina M.; Zaretsky, Michael V.
Abstract: Introduction: Whole exome sequencing (WES) has increasingly become integrated into prenatal care and genetic testing pathways. Current studies of prenatal WES have focused on diagnostic yield. The possibility of obtaining a variant of uncertain significance and lack of provider expertise are frequently described as common barriers to clinical integration of prenatal WES. We describe the implementation and workflow for a multidisciplinary approach to effectively integrate prenatal WES into maternal‐fetal care to overcome these barriers. Methods: A multidisciplinary team reviews and approves potential cases for WES. This team reviews WES results, reclassifying variants as appropriate and provides recommendations for postnatal care. A detailed description of this workflow is provided, and a case example is included to demonstrate effectiveness of this approach. Our team has approved 62 cases for WES with 45 patients ultimately pursuing WES. We have achieved a diagnostic yield of 40% and the multidisciplinary team has played a role in variant interpretation in 50% of the reported variants of uncertain significance. Conclusions: This approach facilitates communication between prenatal and postnatal care teams and provides accurate interpretation and recommendations for identified fetal variants. This model can be replicated to ensure appropriate patient care and effective integration of novel genomic technologies into prenatal settings. Key points: What is already known about the topic? Fetal whole exome sequencing has clinical utility and established yields of 31% across the spectrum of fetal anomalies. Barriers for implementation of prenatal whole exome sequencing include variants of uncertain significance and variant interpretation, lack of provider expertise, and cost of testing. What does this study add? We pilot and describe the workflow for a multidisciplinary approach to prenatal whole exome sequencing to overcome the reported barriers for WES. This model can be replicated on an institutional, local, regional, or national level to improve patient care as whole exome sequencing becomes widespread in prenatal care.